1993
DOI: 10.1093/infdis/168.4.979
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Sequence Diversity and Genomic Clusters of Major Surface Glycoprotein Genes of Pneumocystis carinii

Abstract: The major surface glycoprotein (MSG) of Pneumocystis carinii plays a crucial role in the pathobiology of P. carinii, which often causes fatal pneumonia in AIDS patients. The cDNAs encoding MSG antigens were cloned from a lambda gt11 expression library of rat-derived P. carinii by immunoscreening. The cloned cDNAs constituted a gene family containing approximately 70% amino acid identity between subtypes. The diversity of MSG cDNAs was high and reflected the genomic structure of MSG genes clustered in the P. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 22 publications
5
71
0
Order By: Relevance
“…Through molecular studies of rat and ferret P. carindi, it has been demonstrated that MSG represents a group of proteins encoded by multiple genes (6)(7)(8)19). Numerous unique MSG cDNAs have been identified, establishing that multiple mRNAs are transcribed within a population of organisms (6)(7)(8)(9). These data raise the possibility that antigenic variation may occur in MSG as a means of evading the host immune defenses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through molecular studies of rat and ferret P. carindi, it has been demonstrated that MSG represents a group of proteins encoded by multiple genes (6)(7)(8)19). Numerous unique MSG cDNAs have been identified, establishing that multiple mRNAs are transcribed within a population of organisms (6)(7)(8)(9). These data raise the possibility that antigenic variation may occur in MSG as a means of evading the host immune defenses.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent progress in cloning and expressing MSG genes (6)(7)(8)(9), it should be possible to develop T cell clones, map their epitopes, and test their functional importance in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carindi possesses several carbohydrate-rich surface proteins capable of interacting with lectins and other glycoproteins (35)(36)(37)(38)(39). In particular, P. carinji contains a major surface glycoprotein complex which has been variously termed gpA, gp 95, gpl2O, or major surface glycoprotein (40)(41)(42)(43)(44)(45). Differences in the relative molecular mass of this complex have been related to the host species from which the P. carinii are derived (35).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this, the P. carinii from Chinese SD rats showed 85% homology rate which should be regarded as low homology because α-tubulin DNA is a gene of active translation (Wada et al, 1993). It is necessary to compare the antigenicity of the Chinese isolate.…”
Section: ─156─mentioning
confidence: 94%